Cataract Surgery - Husain Zaidi, Farhan (IntechOpen, 2013)
Cataract is the leading cause of blindness in the world and cataract surgery is the most commonly performed operation worldwide. The international authorship of this book permits discussion of both the generality of the field and the details of a number of important topics that more recent research shows are important to understanding developments in the field of cataract surgery. These topics are discussed under the following areas: Pre-operative Care; Operative Surgery and the History of Cataract Surgery; Complications; and Cataract Surgery in Special Situations. The combination of topics makes this an informative, original, and lasting source of knowledge on cataract surgery. Further the chapters on the history of cataract surgery and major advances in the area are, in particular, of importance not only to surgeons and researchers but to physicians more widely as well as the general reader.